Peter Stuyvesant Collectie. - Pen, J.; Read, Herbert; Schaeffer, Pierre (Amsterdam : Stedelijk Museum Amsterdam, 1962)
Bischof, Peter ; Browne, Michael ; Coetzee, Christo ; Coviello, Peter ; Diederen, Jef ; Ferron, Marcelle ; Heyart, Ben ; Jaffé, Shirley ; Lucebert ; Meijer, Jan ; Müller, Bruno ; Ongenae, Jef ; Perilli, Achille ; Royen, Peter ; Saby, Bernard ; Sitter, Inger ; Whiteley, Brett
biog.[6 p.]
Peter Stuyvesant Collectie, Stedelijk Museum Amsterdam, 18/1 - 12/2 - 1962
Nederlands & Frans & Engels
boek